Effect of Intra-Orifice Depth on Sealing Ability of Four Materials in the Orifices of Root-Filled Teeth: An Ex-Vivo Study - Motaz Ahmad Ghulman; Madiha Gomaa (International Journal of Dentistry)
Aim. To investigate the effect of orifice cavity depth on the sealing ability of Fusio, Fuji II, Fuji IX, and MTA“G”. Materials and Methods. Ninety-two canals in extracted mandibular premolars were prepared, obturated, and randomly grouped into 4 groups. Each group was subgrouped for a 2 mm and 3 mm orifice cavity depth (𝑛=10). The remaining roots were divided to serve as positive and negative controls (𝑛=6). Cavities of the 4 experimental groups were filled with the respective materials and subjected to methylene blue dye leakage. Linear leakage was measured in mm using a stereomicroscope. Statistical Analysis. Kruskall-Wallis test was used at 𝑃<0.05, and t-test was done to compare 2 mm and 3 mm. Results. All tested materials leaked to various degrees. Significantly higher leakage score was found for Fuji IX, Fusio, Fuji II, and MTA “G” in a descending order, when the materials were placed at 3 mm depths. A significant difference was found in the leakage score between the 2 mm and 3 mm depths in all tested materials with the 3 mm depth showing a greater leakage score in all tested materials. Exception was in MTA “G” at 2 mm and 3 mm depths (0.551 mm ± 0.004 mm and 0.308 mm ± 0.08 mm, resp.). Conclusion. The null hypothesis should be partially rejected. Fusio and MTA “G” were affected by orifice cavity depth with regard to their sealing ability. MTA “G” had the least leakage when placed at 2 or 3 mm depths, and Fusio is the next when placed at 2 mm depth. Two millimeters orifice cavity depth is suitable for most adhesive orifice barrier materials.